Early-career general practitioners' perceptions of the utility of vocational training for subsequent independent practice. Issue 2 (4th March 2023) - Tran, Michael; Wearne, Susan; Fielding, Alison; Moad, Dominica; Tapley, Amanda; Holliday, Elizabeth; Ball, Jean; Davey, Andrew; van Driel, Mieke; FitzGerald, Kristen; Spike, Neil; Bentley, Michael; et al.
ABSTRACT: Purpose: To evaluate Australian early-career general practitioners' perceptions of the utility of their prior vocational training in preparing them for independent specialist practice. We hypothesised that in-practice teaching would be perceived as more useful than formal education delivered by Regional Training Organisations (RTOs). Methods and materials: A cross-sectional questionnaire-based study of early-career general practitioners (RTO 'alumni'). The outcomes were Likert scale ratings of alumni's perceived impact of RTO education versus in-practice training on their preparedness for independent practice. Ratings were compared using Wilcoxon signed-rank tests. Multivariable linear regression was used to establish alumni characteristics associated with perceptions of utility of in-practice versus RTO-delivered education. Results: Three hundred and fifty-four alumni responded (response rate 28%). In-practice training was rated statistically significantly higher than RTO education for minor procedural skills, teaching skills, professional responsibilities, tolerating clinical uncertainty, and preparing for managing child and adolescent health, aged care, chronic disease, multi-morbidity and mental health. RTO education rated higher than in-practice training for practising evidence-based medicine and Aboriginal and Torres Strait Islander health. For a number of further areas, there was no statistically significant difference in alumni ratings of utility. Conclusions: In-practice or RTO-led teaching was perceived as more useful for some components of independent practice, whilst for others there was no significant difference. The findings support recognition of the individual educational components of a blended education/training structure.